Peran Biaya Operasional Pendidikan terhadap Output Pendidikan - Muhammad Imad; Hamdan Herdiawan (MANAZHIM, 2019)
Operational Education Costs are one of the most important instrumental input components in the administration of education. The education process cannot run without the support of operational costs. Madrasah Aliyah is a formal education unit under the auspices of the Ministry of Religion which organizes general education with the distinctiveness of the Islamic religion at the secondary education level. Educational activities carried out by schools including Madrasah Aliyah must be based on the educational goals to be achieved. One of the achievement of educational goals can be seen from the results of learning or educational output. Parents of students dare to pay high education costs not to obtain low educational output, but they want high educational output. The purpose of this study was to determine the role of the operational costs of education on educational output in Madrasah Aliyah in Cimahi. This research uses descriptive study method, because the problem under study is an actual and factual so that the researcher is able to study intensively about the background of the present situation. In this study the authors used several data collection techniques, namely observation, interviews and documentation studies. In this study there are 2 Aliyah Madrasas which are used as sample objects for comparison so that researchers know the role of educational operational costs to educational output, namely Madrasah Aliyah Mutiteknik Asih Putera and Madrasah Aliyah Al-Farisy. While the educational output in this study is seen from the average value of NEM for the National Examination of students from each school. From various data obtained by the author about the object of research, the results of the study indicate that the role of operational operational costs in this research has an influence on educational output. This means that high operational costs of education on average result in better educational outputs.